Stopping the error cascade: a report on ameliorators from the ASIPS collaborative. Issue 1 (14th February 2007) - Parnes, Bennett; Fernald, Douglas; Quintela, Javán; Araya-Guerra, Rodrigo; Westfall, John; Harris, Daniel; Pace, Wilson
Abstract : Objective: To present a novel examination of how error cascades are stopped (ameliorated) before they affect patients. Design: Qualitative analysis of reported errors in primary care. Setting: Over a three-year period, clinicians and staff in two practice-based research networks voluntarily reported medical errors to a primary care patient safety reporting system, Applied Strategies for Improving Patient Safety (ASIPS). The authors found a number of reports where the error was corrected before it had an adverse impact on the patient. Results: Of 754 codeable reported events, 60 were classified as ameliorated events. In these events, a participant stopped the progression of the event before it reached or affected the patient. Ameliorators included doctors, nurses, pharmacists, diagnostic laboratories and office staff. Additionally, patients or family members may be ameliorators by recognising the error and taking action. Ameliorating an event after an initial error requires an opportunity to catch the error by systems, chance or attentiveness. Correcting the error before it affects the patient requires action either directed by protocols and systems or by vigilance, power to change course and perseverance on the part of the ameliorator. Conclusion: Despite numerous individual and systematic methods to prevent errors, a system to prevent all potential errors is not feasible. However, a more pervasive culture of safety that builds on simple acts in addition to more costly and complex electronic systems may improve patient outcomes. Medical staff and patients who are encouraged to be vigilant, ask questions and seek solutions may correct otherwise inevitable wrongs.